Coating method of titanium alloy wire surface coating for fastener
By adopting a double-layer dry film lubricant system and coating penetration technology on the titanium alloy wire, the problem of poor wear resistance of single-layer thermoset dry film lubricant at high temperature is solved, and the titanium alloy wire is realized under high temperature conditions. Low friction performance and wear resistance meet the demanding requirements in the aerospace field.
Patent Information
- Application Number
- CN202411659928.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the upsetting temperature of existing titanium alloy wire materials reaches above 700℃, the single-layer thermoset dry film lubricant has poor high temperature resistance, resulting in problems such as sticking, straining and mold damage. There is a lack of effective solutions in China.
Using a double-layer dry film lubricant system, first coat a layer of dry film lubricant A on the surface of the titanium alloy wire, then superimpose a layer of dry film lubricant B, and through the coating penetration process, the modified aldehyde ketone resin and Materials such as graphite enhance the bonding force and high temperature resistance of the coating through heating, ultrasonic and ion exchange resin treatment.
It significantly improves the high-temperature lubrication performance of titanium alloy wire, meets the high lubrication needs under extreme conditions of aerospace, improves the insufficient performance of a single lubricant at high temperature, and ensures the titanium alloy wire under conditions of 760~800℃. Low friction coefficient extends wear-resistant life during the upsetting process.
Smart Images

Figure CN119140400A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloy wire coating, and in particular relates to a coating method for a titanium alloy wire surface coating for a fastener. Background Art
[0002] As the demand for titanium and titanium alloy products in the aviation and aerospace fields continues to increase, the lubrication requirements for upstream titanium alloy wires used in riveting titanium alloy fasteners for base structures have also increased. Due to the poor wear resistance of titanium and titanium alloys, in order to prevent mutual friction and adhesion of base metals during the upsetting process, it is usually necessary to coat a layer of dry film lubricant on the surface of titanium alloy wires to increase the lubrication performance of titanium alloy wires, reduce the friction coefficient of titanium alloy wires, and improve the assembly process performance of titanium alloy wires.
[0003] Usually, a single layer of thermosetting dry film lubricant is coated on the surface of titanium alloy wire. The main components of the single layer of thermosetting dry film lubricant are silicone resin and solid lubricating materials. The solid lubricating material is usually a mixture of molybdenum disulfide and graphite. In order to improve the high temperature resistance of the single layer of thermosetting dry film lubricant, the conventional method is to modify the silicone resin by physical or chemical means, or replace the solid lubricating material, which can improve the heat resistance of the overall thermosetting dry film lubricant to a certain extent; however, studies have shown that when the upsetting temperature reaches above 700°C, the surface of the titanium alloy wire will still have problems such as sticking to the mold, pulling and mold damage, and there is currently no better way to solve this problem in China. Summary of the invention
[0004] The object of the present invention is to provide a coating method for the surface coating of titanium alloy wire for fasteners, so as to solve the problem that the high temperature resistance of the single-layer thermosetting dry film lubricant is poor when the existing upsetting temperature reaches above 700°C.
[0005] The present invention adopts the following technical solution: a coating method for the surface coating of a titanium alloy wire for fasteners, which is specifically implemented according to the following steps: Step 1, cleaning the surface of the titanium alloy wire to be coated, and then performing sandblasting on the surface of the titanium alloy wire to be coated; Step 2, coating a layer of dry film lubricant A on the surface of the titanium alloy wire treated in step 1, and after the dry film lubricant A is dried, coating a layer of dry film lubricant B on the dry film lubricant A; Step 3, performing a coating penetration process on the titanium alloy wire treated in step 2; The specific process of the coating penetration process is: the titanium alloy wire treated in step 2 is passed through a heating furnace, an ultrasonic device and an ion exchange resin in sequence to perform heating, vibration and ion exchange treatment on the titanium alloy wire, and finally a finished titanium alloy wire with coating treatment is obtained; The dry film lubricant A contains 5-10% by mass of polyethylene glycol, and the dry film lubricant B contains 5-15% by mass of a modified aldehyde-ketone resin, wherein the polyethylene glycol is used to form hydrogen bonds with the modified aldehyde-ketone resin under electrostatic adsorption; The synthesis method of the modified aldehyde-ketone resin is: fully dissolve the silicone resin with acetonitrile, then add 30% hydrogen peroxide dropwise, and stir evenly at 30~70°C in a sealed environment to obtain the modified aldehyde-ketone resin; the side chain of the silicone resin has N,N-dimethyl, and the mass ratio of the silicone resin to the hydrogen peroxide is (50~100):1.
[0006] Furthermore, the dry film lubricant B is prepared by mixing the following raw materials in mass fractions: 10-50% of graphite, 20-30% of polyvinyl alcohol, 5-15% of modified aldehyde-ketone resin, 1-2% of defoaming agent, and the balance is distilled water.
[0007] Furthermore, the dry film lubricant A is prepared by mixing the following raw materials in mass fractions: 20-40% of a mixture of molybdenum disulfide and graphite, 15-30% of sodium silicate, 10-25% of an organic silicone resin, 5-10% of polyethylene glycol, 3-10% of a suspension stabilizer, 1-2% of a defoamer, and the balance is distilled water.
[0008] Furthermore, the performance of dry film lubricant A and dry film lubricant B meet the following requirements: solid content of 30-50%, pH value ≥ 9, surface drying time of 20-30 min, and adhesion level 0-1; Among them, the density of dry film lubricant A is 1.15~1.2g / cm 3 , the density of dry film lubricant B is 1.35~1.50g / cm 3 .
[0009] Furthermore, in the coating penetration process, the temperature of the heating furnace is 100~300°C, the working current and working temperature of the ultrasonic device are 1~5A and 25~70°C respectively, and the ion exchange resin selected is a weakly alkaline anion exchange resin system.
[0010] Furthermore, the sandblasting in step 1 specifically uses corundum with a particle size of 50-250 μm, and the surface roughness of the titanium alloy wire after sandblasting is Ra=1.0-3.0 μm.
[0011] The beneficial effects of the present invention are as follows: the present application provides a dry film lubricant A as a thermosetting dry film lubricant, and a layer of dry film lubricant B is applied on the outside of the dry film lubricant A, wherein the dry film lubricant B includes a modified aldehyde-ketone resin; since the modified aldehyde-ketone resin contains a carbonyl functional group, the oxygen atom in the carbonyl functional group has a large electronegativity, the oxygen atom carries a partial negative charge, and the carbon atom in the carbonyl functional group carries a partial positive charge, the carbonyl group forms a dipole, and a dipole-dipole interaction occurs, thereby making the molecules in the modified aldehyde-ketone resin firmly bonded, so the dry film lubricant B has better high temperature resistance than the dry film lubricant A; and since the modified aldehyde-ketone resin in the dry film lubricant B can form hydrogen bonds with the hydrogen ions in the dry film lubricant A under electrostatic adsorption, the two dry film lubricants cooperate with each other, further enhancing the bonding force of the coatings of the two, making up for the poor high temperature resistance of the single lubricating coating A, meeting the high lubrication performance under extremely harsh conditions in aerospace, and improving the problems of the harsh application conditions and poor high temperature lubrication performance of the single lubricant. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a scanning electron microscope image of the coating of the finished titanium alloy wire obtained in Example 1; Figure 2 This is a scanning electron microscope image of the coating of the finished titanium alloy wire obtained in Example 2; Figure 3 This is a scanning electron microscope image of the coating of the finished titanium alloy wire obtained in Example 3; Figure 4-a This is a data graph of the friction coefficient of the finished titanium alloy wire obtained in Example 1 measured by a friction test at an ambient temperature of 760°C; Figure 4-b This is a data graph of the friction coefficient of the finished titanium alloy wire obtained in Example 2 measured by a friction test at an ambient temperature of 780°C; Figure 4-c The friction coefficient data diagram of the titanium alloy wire product obtained in Example 3 is measured by a friction test at an ambient temperature of 800°C; Figure 4-d The friction coefficient data graph is obtained by conducting a friction test on uncoated titanium alloy wire products at room temperature; Figure 4-e The friction coefficient data graph of the finished titanium alloy wire with a single layer of coating was measured in a friction test at a temperature of 760°C. Figure 5 is a structural diagram of the carbonyl functional group in the modified aldehyde-ketone resin of the present invention; Figure 6 Schematic diagram of the intermolecular forces between the dry film lubricant A and the dry film lubricant B of the present invention. DETAILED DESCRIPTION
[0013] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0014] The present invention provides a coating method for a titanium alloy wire surface for a fastener, which is specifically implemented according to the following steps: Step 1, pretreatment of titanium alloy wire: clean the dust and dirt on the surface of the titanium alloy wire to be coated, and then sandblast the surface of the titanium alloy wire. The pretreatment of the titanium alloy wire before coating is to improve the adhesion of the dry film lubricant coating. Use cleaning products to thoroughly clean the surface to be coated to remove dust and dirt. Then use a sandblasting machine to sandblast the surface of the titanium alloy wire to improve the bonding strength between the substrate and the coating and extend the wear life.
[0015] Step 2: coating a layer of dry film lubricant A on the surface of the titanium alloy wire treated in step 1, and coating a layer of dry film lubricant B on the dry film lubricant A after the dry film lubricant A is dried.
[0016] The dry film lubricant A contains 5-10% by mass of polyethylene glycol, and the dry film lubricant B contains 5-15% by mass of a modified aldehyde-ketone resin. The polyethylene glycol is used to form hydrogen bonds with the modified aldehyde-ketone resin under electrostatic adsorption.
[0017] The synthesis method of the modified aldehyde-ketone resin is: fully dissolve the silicone resin with acetonitrile, then add 30% hydrogen peroxide dropwise, and stir evenly at 30~70°C in a sealed environment to obtain the modified aldehyde-ketone resin; the side chain of the silicone resin has N,N-dimethyl, and the mass ratio of the silicone resin to the hydrogen peroxide is (50~100):1.
[0018] Before the coating process is implemented, the dry film lubricant A needs to be fully stirred until there is no stratification and the solid particles on the surface are evenly distributed, and then the titanium alloy wire is coated with an automatic coating machine. By controlling the various parameters of the coating machine, the surface coating is complete and uniform in thickness, and the subsequent upsetting requirements are met.
[0019] Step 3, performing a coating infiltration process on the titanium alloy wire treated in step 2. The specific process of the coating infiltration process is: passing the titanium alloy wire treated in step 2 through a heating furnace, an ultrasonic device and an ion exchange resin in sequence to perform heating, vibration and ion exchange treatment on the titanium alloy wire accordingly, and finally obtaining a finished titanium alloy wire after the coating treatment.
[0020] Specifically, there is a channel in the heating furnace for the titanium alloy wire to pass through, and the titanium alloy wire is heated when passing through the heating furnace. The ultrasonic device is installed in the vibrating water pool, and the titanium alloy wire vibrates when passing through the vibrating water pool. The ion exchange resin is installed in the exchange water pool, and the weak alkaline anions of the ion exchange resin can adsorb the hydroxyl anions dissociated from the dry film lubricant A when the titanium alloy wire passes through the exchange water pool. After the dry film lubricant A is polarized by the ion exchange resin, a large number of free H ions will be generated. These H ions can form hydrogen bonds with the dry film lubricant B under electrostatic attraction, further enhancing the bonding force of the two layers of coating, making the bonding between the titanium alloy substrate and the coating, and between the coatings more firmly, and avoiding the peeling phenomenon after the coating is cured.
[0021] In summary, ultrasonic treatment and ion exchange reaction under high temperature conditions promote the molecular movement and spatial distribution inside the coating, making the two coating layers formed by dry film lubricant A and dry film lubricant B more firmly bonded.
[0022] The surface coating state and coating thickness of the titanium alloy wire products after final coating are inspected by visual inspection and infrared diameter gauge. For example: the coating thickness error of a single material is ≤3μm, the batch dimensional stability of the coating thickness Cv is ≤3%, the friction coefficient is ≤0.2, there is no sticking film phenomenon, and the coating surface is complete, black and shiny without nodules.
[0023] In some embodiments, dry film lubricant B is prepared by mixing the following raw materials in mass fraction: 10-50% graphite, 20-30% polyvinyl alcohol, 5-15% modified aldehyde-ketone resin, 1-2% defoamer, and the balance is distilled water. Polyvinyl alcohol can improve the adhesion of the coating and the water resistance of the coating, and reduce the shedding and foaming of the coating in a humid environment. The preparation method of dry film lubricant B is: add the above raw materials to the reactor in sequence, stir at a constant speed for 2-5 hours at 30-60°C and normal pressure to obtain dry film lubricant B, and the speed of the magnetic stirrer of the reactor is 300-500rmp.
[0024] In some embodiments, dry film lubricant A is prepared by mixing the following raw materials in mass fractions: 20-40% of a mixture of molybdenum disulfide and graphite, 15-30% of sodium silicate, 10-25% of an organosilicon resin, 5-10% of polyethylene glycol, 3-10% of a suspension stabilizer, 1-2% of a defoamer, and the remainder is distilled water. The suspension stabilizer may be organic bentonite or silica, etc., which is used to stabilize the dispersion of the dry film lubricant and improve storage stability. Polyethylene glycol can improve the construction performance of the coating and facilitate coating and drying. The preparation method of dry film lubricant A is as follows: the above raw materials are added to a reactor in sequence, and the dry film lubricant A is obtained after uniform stirring for 1-6 hours at 30-40°C and normal pressure. The speed of the magnetic stirrer of the reactor is 300-500 rpm.
[0025] In some embodiments, the state, composition, and performance of dry film lubricant A and dry film lubricant B need to be inspected in accordance with the factory inspection procedures, and subsequent processes can only be carried out after meeting the requirements. The performance of dry film lubricant A and dry film lubricant B must meet the following requirements: solid content of 30~50%, pH value ≥9, surface drying time of 20~30min, and adhesion of 0~1 level. Among them, the density of dry film lubricant A is 1.15~1.2g / cm 3 , the density of dry film lubricant B is 1.35~1.50g / cm 3 .
[0026] The parameters of density and solid content are set to ensure the thickness requirements of the coating; the pH value ≥ 9 is because the additives in dry film lubricant A and dry film lubricant B can only remain stable in an alkaline environment; the surface drying time is to further improve production efficiency and ensure good construction performance; adhesion meeting level 0~1 is the basic requirement of the coating.
[0027] In some embodiments, the temperature of the heating furnace involved in the coating penetration process is 100~300℃, and the heating furnace can fully preheat the titanium alloy wire, thereby accelerating the intermolecular movement. The working current and working temperature of the ultrasonic device are 1~5A and 25~70℃ respectively. On the one hand, the ultrasonic device can wash away the dust on the surface of the coating, and on the other hand, it can also induce the generation of intermolecular binding force through the oscillation effect. The ion exchange resin used is a weakly alkaline anion exchange resin system. The ion exchange resin can induce the arrangement of the electron cloud density between molecules, further promote the formation of hydrogen bonds between the two layers of coating, and avoid the peeling of the surface coating after curing.
[0028] In some embodiments, the sandblasting in step 1 specifically uses corundum with a particle size of 50-250 μm. The surface roughness of the titanium alloy wire after sandblasting is Ra=1.0-3.0 μm. The sandblasting makes the bonding strength between the substrate and the coating of the titanium alloy wire higher.
[0029] In the prior art, when the upsetting working temperature is ≥480°C, the solid lubricating material molybdenum disulfide in the dry film lubricant A will undergo an oxidation reaction to generate molybdenum trioxide. If the single dry film lubricant A coating is modified, it can only be guaranteed that the silicone resin will not crack or fail under high temperature conditions. Therefore, in order to avoid the weakening of wear resistance caused by the oxidation failure of molybdenum disulfide as a solid lubricating material under high temperature conditions above 480°C, the present invention superimposes a layer of dry film lubricant B with graphite as the solid lubricating material on the basis of A.
[0030] Because the silanol groups on the molecular chains of silicone resins will act as reaction sites to undergo self-polymerization or copolymerization under high temperature and oxygen conditions, causing the molecular weight of the silicone resin to continue to decrease and lose weight, thus affecting the performance of the silicone resin under high temperature conditions. Therefore, modified aldehyde-ketone resins are used in dry film lubricant B, and the silanol groups of the modified aldehyde-ketone resins will be blocked at the end by the reaction byproducts during the modification, thereby losing their reaction activity. At the same time, the carbonyl functional groups are introduced into the modified aldehyde-ketone resins to induce the generation of intermolecular forces, thereby improving the high temperature resistance of the dry film lubricant. Figure 5 As shown, the modified aldehyde-ketone resin contains a carbonyl functional group, the oxygen atom in the carbonyl functional group has a large electronegativity, the oxygen atom carries a partial negative charge, and the carbon atom in the carbonyl functional group carries a partial positive charge. The carbonyl group forms a dipole, and a dipole-dipole interaction occurs, so that the molecules in the modified aldehyde-ketone resin are firmly bonded. Therefore, the high temperature resistance of dry film lubricant B is better than that of dry film lubricant A.
[0031] In the coating penetration process, the weakly alkaline anions of the ion exchange resin can induce the dissociation of hydroxyl anions in the dry film lubricant A. Figure 6 As shown in the figure, after the dry film lubricant A is polarized by the ion exchange resin, a large number of free H ions will be generated. These H ions can form hydrogen bonds with the dry film lubricant B under electrostatic attraction. The two dry film lubricants work together to further enhance the bonding force of the two coatings, making up for the poor high temperature resistance of the single lubricating coating A. It can meet the high lubrication performance under extremely harsh conditions in aerospace, and improve the problems of harsh application conditions and poor high temperature lubrication performance of single lubricants.
[0032] Embodiment: The present invention provides three embodiments, namely, Embodiment 1 to Embodiment 3, each of which is implemented according to the following steps: Step 1, cleaning the surface of the titanium alloy wire to be coated, and then sandblasting the surface of the titanium alloy wire; Step 2, coating a layer of dry film lubricant A on the surface of the titanium alloy wire treated in step 1, and after the dry film lubricant A is dried, coating a layer of dry film lubricant B on the dry film lubricant A; Step 3, performing a coating penetration process on the titanium alloy wire treated in step 2; The specific process of the coating penetration process is: the titanium alloy wire treated in step 2 is passed through a heating furnace, an ultrasonic device and an ion exchange resin in sequence to perform heating, vibration and ion exchange treatment on the titanium alloy wire accordingly, and finally a finished titanium alloy wire with coating treatment is obtained.
[0033] The raw material selection of dry film lubricant A and dry film lubricant B, and the process parameters involved in each step are shown in Table 1.
[0034] Figure 1-Figure 3 The coating scanning electron microscope images of the titanium alloy wires after coating in Example 1 to Example 3 are shown respectively. The coating thickness error of a single strand can be calculated from the difference between the maximum coating thickness and the minimum coating thickness in the image. The specific values are shown in Table 2. As can be seen from Table 2, the coating thickness error of a single strand of the titanium alloy wire products obtained in the three examples is ≤3, the batch dimensional stability is ≤3, and there is no sticking phenomenon.
[0035] Table 1 Process parameters involved in each step in Example 1 to Example 3
[0036] Table 2 Finished product properties of three embodiments
[0037] In order to characterize the high temperature resistance of the coating, the titanium alloy wire product prepared in Example 1 was subjected to a friction test at an ambient temperature of 760°C, the titanium alloy wire product prepared in Example 2 was subjected to a friction test at an ambient temperature of 780°C, the titanium alloy wire product prepared in Example 3 was subjected to a friction test at an ambient temperature of 800°C, the uncoated titanium alloy wire was subjected to a friction test at room temperature as a blank control group, and the titanium alloy wire product with a single layer of coating in the prior art was subjected to a friction test at 760°C. The final friction test results correspond to the following: Figure 4-a to Figure 4-e In the friction experiment, the GCr15 bearing steel ball with a diameter of 6 mm was used as the friction pair to make reciprocating circular motion on the coating surface, with a friction radius of 2 mm, a load of 2 N, a rotation speed of 280 rpm, and a wear time of 1 min.
[0038] Depend on Figure 4-d It can be seen that under room temperature conditions, the friction coefficient of the surface of the titanium alloy wire without coating in the blank group fluctuates greatly, and the friction coefficient is stable at 0.6. Figure 4-e It can be seen that the friction coefficient of the finished titanium alloy wire with a single layer of coating is basically stable at 0.4 in an environment of 760°C. Figure 4-a to Figure 4-c It can be seen that the friction coefficients of the finished titanium alloy wires of the three embodiments obtained by the method of the present invention are all less than 0.2, and much less than 0.6.
[0039] Under the same test conditions, the lower the friction coefficient, the better the friction reduction of the titanium alloy wire. Based on the above friction test results, the following conclusions can be drawn: Under high temperature conditions of 760°C, the friction coefficient of the finished titanium alloy wire with a single layer of coating is lower than the friction coefficient of the finished titanium alloy wire without coating at room temperature. However, under the same temperature conditions, the friction coefficient of the single-coated titanium alloy wire is greater than that of the double-coated titanium alloy wire. This further illustrates that the single coating can reduce friction to a certain extent, but when the upsetting temperature is greater than 700°C, the single coating does not reflect good high-temperature friction reduction performance. The double-coated titanium alloy wire of this embodiment has a friction coefficient of less than 0.2 under the conditions of 760~800°C, which is much smaller than the friction coefficient of the blank control group, indicating that the titanium alloy wire obtained in this embodiment has excellent high temperature resistance and can meet the requirements of high-temperature upsetting of titanium alloy wire in the aerospace field.
Claims
1. A coating method for a titanium alloy wire surface coating for fasteners, It is characterized in that Follow the steps below to implement it: Step 1, cleaning the surface of the titanium alloy wire to be coated, and then performing sandblasting on the surface of the titanium alloy wire to be coated; Step 2, coating a layer of dry film lubricant A on the surface of the titanium alloy wire treated in step 1, and after the dry film lubricant A is dried, coating a layer of dry film lubricant B on the dry film lubricant A; Step 3, performing a coating penetration process on the titanium alloy wire treated in step 2; The specific process of the coating penetration process is: the titanium alloy wire treated in step 2 is passed through a heating furnace, an ultrasonic device and an ion exchange resin in sequence to perform heating, vibration and ion exchange treatment on the titanium alloy wire accordingly, and finally a finished titanium alloy wire with a coating treatment is obtained; The dry film lubricant A contains 5-10% by mass of polyethylene glycol, and the dry film lubricant B contains 5-15% by mass of a modified aldehyde-ketone resin, wherein the polyethylene glycol is used to form hydrogen bonds with the modified aldehyde-ketone resin under electrostatic adsorption; The synthesis method of the modified aldehyde-ketone resin is as follows: the silicone resin is fully dissolved by acetonitrile, and then 30% hydrogen peroxide is added dropwise, and the modified aldehyde-ketone resin is obtained after being stirred evenly at 30-70° C. in a sealed environment; the side chain of the silicone resin has N,N-dimethyl, and the mass ratio of the silicone resin to hydrogen peroxide is (50-100):
1.
2. A method for coating a surface coating of a titanium alloy wire for fasteners according to claim 1, It is characterized in that The dry film lubricant B is prepared by mixing the following raw materials in mass fractions: 10-50% of graphite, 20-30% of polyvinyl alcohol, 5-15% of modified aldehyde-ketone resin, 1-2% of defoamer, and the balance is distilled water.
3. A method for coating a surface coating of a titanium alloy wire for fasteners according to claim 2, It is characterized in that The dry film lubricant A is prepared by mixing the following raw materials in mass fractions: 20-40% of a mixture of molybdenum disulfide and graphite, 15-30% of sodium silicate, 10-25% of an organic silicone resin, 5-10% of polyethylene glycol, 3-10% of a suspension stabilizer, 1-2% of a defoamer, and the balance is distilled water.
4. A method for coating a surface coating of a titanium alloy wire for fasteners according to any one of claims 1 to 3, It is characterized in that The properties of the dry film lubricant A and the dry film lubricant B meet the following requirements: solid content of 30-50%, pH value ≥ 9, surface drying time of 20-30 minutes, and adhesion level 0-1; Wherein, the density of the dry film lubricant A is 1.15~1.2g / cm 3 The density of the dry film lubricant B is 1.35-1.50 g / cm 3 .
5. A method for coating a surface coating of a titanium alloy wire for fasteners according to any one of claims 1 to 3, It is characterized in that In the coating penetration process, the temperature of the heating furnace is 100-300° C., the working current and working temperature of the ultrasonic device are 1-5A and 25-70° C. respectively, and the ion exchange resin selected is a weakly alkaline anion exchange resin system.
6. A method for coating the surface of a titanium alloy wire for fasteners according to any one of claims 1 to 3, It is characterized in that The sandblasting in step 1 specifically uses corundum with a particle size of 50-250 μm, and the surface roughness of the titanium alloy wire after sandblasting is Ra=1.0-3.0 μm.
Citation Information
Patent Citations
Anti-radiation high-temperature-resistant lubricating material and preparation method and application thereof
CN112048351A
High-temperature-resistant and high-lubrication coating for aviation fastener wire and application of high-temperature-resistant and high-lubrication coating
CN116769334A
High-temp. dry film lubricant
CN1212284A
Silicone resin bonded dry film lubricants
US20030224947A1
Lubricant coating for expandable tubular members
US6695012B1
